Customer relationship management (CRM) technology and organization performance: Is marketing capability a missing link? An empirical study in the Malaysian hotel industry - Mohammed, Abdul Alem; Rashid, Basri; Tahir, Shaharuddin (Canadian Center of Science and Education, 2014)
Due to the aggressive market competition in hotel sector, it is critical that hotels should adopt new strategy like CRM technology to assist hotel employees, serve customers better and improve organization performance.However, prior studies indicated that the relationship between CRM technology and organization performance is equivocal.These mixed results may be to a lack of understanding of the mechanisms that link CRM technology and organization performance.For this reason, the study used marketing capabilities (planning and implementation) as mediators between CRM technology and organization performance. The study surveyed a sample of 447 hotels firm in Malaysia and used correlation and regression for analyses and testing. The findings suggest that CRM technology is associated with the four dimensions of organization performance (i.e. financial, customer, internal process and learning and growth). In addition the findings reveal that marketing capabilities (planning and implementation) play a mediator role in the relationship between CRM technology and various dimensions of organization performance.